Some properties of solutions of two-choice and three-choice problems of dynamic programming for infinite stage processes - Bistrickas, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Б. Бистрицкас. Некоторые свойства бесконечношагового дихотомического и трихотомического процесса динамического программирования V. Bistrickas. Kai kurios dinaminio programavimo dichotominio ir trichotominio proceso su begaliniu žingsnių skaičiumi savybės